Penetapan kadar gentamisin dalam sediaan krim dengan kromatografi lapis tipis - densitometri - Haryanto, Isnaeni Yudi; Burhanudin, Achmad; poernomo, Achmad toto (Pharmaciana, 2016)
The used of Gentamicin is still regarded for overcoming infectious diseases. Several preparations of the gentamicin are available in the market as injection, eye or ear drops, and topical dosage forms. Based on the standard method, determination of the gentamicin is carried out by microbiological assay. Several instrumental method have been reported. In this research, Thin Layer Chromatography-Densitometry (TLC-Densitometry) has been validated and used for determining gentamicin in cream dosage form. The TLC was carried out on a Silica gel GF254 using KH2PO4 20% and ninhidrin 2% solution (in ethanol 96%) as eluent and spots visualization respectively. Three spots appeared on the chromatogram having Rf value 0.51, 0.47, and 0.36. All the spots gave maximum absorption at 400 nm. The spot with Rf value of 0.51 was the highest intensity. Limit of Detection (LoD) and Limit of quantitation (LoQ) of the major component was 0.019 and 0.064 respectively. The other validation characteristics met the requirement for determination of gentamicin in the cream dosage form.